Anatomical considerations and clinical implications of bicipital aponeurosis: A magnetic resonance imaging study. Issue 3 (11th April 2022) - Balaban, Mehtap; Torun, Bilge İpek
Abstract: The bicipital aponeurosis (BA) is the distal aponeurosis of the biceps brachii which usually covers the median nerve (MN), and the brachial artery (BrA) and sometimes causes compression of these structures. Since these situations are rarely reported in the literature, BA frequently does not come to mind as a cause of such compression. Therefore, the diagnosis may be delayed. In this study, we aimed to investigate the morphometry of BA and its relationship with the surrounding neurovascular structures and to draw attention to BA as a structure that can cause entrapment of the MN and rarely, the BrA. We examined the MRIs of the elbow of 279 patients (107 women, 172 men) aged between 18 and 72 years. We measured the thickness, length and width of BA, and investigated the anatomical relationship between BA, BrA, and MN. The respective median thickness, width, and length of BA were 0.7 (0.4–1.8 mm), 18.0 (6.0–34.0 mm), and 32.0 (18.0–50.0 mm), respectively. In all sections examined, the BA covered the BrA and MN, and was located immediately anterior to the BrA. In 225 (80.6%) of 279 MRIs, the BrA was located anterior to the MN and posterior to the BA. In the remaining 54 (19.4%) MRIs, the MN was located anterior to the BrA and posterior to the BA. The respective median thickness, width, and length of the BA were 0.7 mm, 18.0 mm, and 32.0 mm, respectively. It covered the BrA and MN and was located immediately anterior to the BrA. The BA sometimes causes compression syndromes of these structures, therefore, for physicians, it is important to understand the anatomy of the BA.